Hybrid endoscopic mucosal resection and full-thickness resection for large colonic polyps harboring a small focus of invasive cancer: a case series - Chua, Jamie S.; Dang, Hao; Zwager, Liselotte W.; Dekkers, Nik; Hardwick, James C. H.; Langers, Alexandra M. J.; van der Kraan, Jolein; Perk, Lars E.; Bastiaansen, Barbara A. J.; Boonstra, Jurjen J.; on behalf of the Dutch eFTR Working Group (Endoscopy International Open, 2021)
Endoscopic treatment of large laterally spreading tumors (LSTs) with a focus of submucosally invasive colorectal cancer (T1 CRC) can be challenging. We evaluated outcomes of a hybrid resection technique using piecemeal endoscopic mucosal resection (pEMR) and endoscopic full-thickness resection (eFTR) in patients with large colonic LSTs containing suspected T1 CRC. Six hybrid pEMR-eFTR procedures for T1 CRCs were registered in a nationwide eFTR registry between July 2015 and December 2019. In all cases, the invasive part of the lesion was successfully isolated with eFTR; with eFTR, histologically complete resection of the invasive part was achieved in 5 /6 patients (83.3 %). No adverse events occurred during or after the procedure. The median follow-up time was 10 months (range 6–27), with all patients having undergone ≥ 1 surveillance colonoscopy. One patient had a small adenomatous recurrence, which was removed endoscopically. In conclusion, hybrid pEMR-eFTR is a promising noninvasive treatment modality that seems feasible for a selected group of patients with large LSTs containing a small focus of T1 CRC.